Composite materials based on fine-dispersed Al2O3 with enhanced physical and mechanical properties. (December 2019) - Gevorkyan, E S; Rucki, M; Torosyan, K S; Kislitsa, M V; Gutsalenko, Yu G
Abstract: Ceramic nanocomposites of silicon carbide reinforced Al2 O3 are obtained by electroconsolidation. Mechanical properties are investigated and their dependencies on the composition and consolidation modes are shown over a wide range. The optimal composition and modes of electrical consolidation for the Al2 O3 -SiC composite are revealed. A criterion for choosing a material for instrumental application, which takes into account the basic properties of the cutting tool, is proposed. Comparison of the obtained composites with similar materials used for the manufacture of tool products including global manufacturers has been carried out.